Pharmacy students' lived experiences of the mental health support structure at Rhodes University - Dabengwa, Nqobani Mathew (https://orcid.org/0000-0002-7620-9674) (Rhodes University, 2026)
Mental health is a global concern and an increasingly important issue at universities as students face unique stressors that can significantly impact their wellbeing. Academic pressures, social challenges, and financial constraints contribute to a high prevalence of mental health issues among university students. Effective support structures are crucial in helping students navigate these challenges and maintain their mental health. This study examined the mental health support structures available to pharmacy students at Rhodes University, as well as the students' perceptions of their effectiveness and the challenges they face in accessing these services. The research employed a constructivist-interpretivist approach, phenomenology, and the Health Policy and Systems Research (HPSR) framework to gain a comprehensive understanding of students’ lived experiences and perceptions of the available mental health support structures and services at the university. Data collection and analysis were conducted in two phases. The first phase involved analysing accessible university documents related to mental health policies and support services. In the second phase, a phenomenological approach was employed, and qualitative interviews were conducted with a stratified purposive sample of pharmacy students to gather in-depth insights into their experiences and perceptions. These interviews explored students’ perceived need for mental health support, as well as the availability and accessibility of such services at the University. For data analysis, a thematic approach was employed to identify, analyse, and report patterns within the data. Interview responses were transcribed and uploaded into ATLAS.ti®, a qualitative data analysis software. A coding scheme was developed based on the research questions and emerging themes. The data were coded and organised into categories to explore recurring themes and patterns in-depth. Document analysis was also conducted using relevant university policies, guidelines and supplementary materials on mental health policies and support services. The data were coded to provide contextual understanding and complement the interview findings. The findings revealed that although mental health support services were available at the university, students experienced significant barriers to access, including long waiting times, limited awareness of services, stigma associated with help-seeking, and concerns about confidentiality. Academic pressure, financial stress, and emotional distress were identified as major contributors to poor mental health. While some students reported positive experiences with counselling services, many perceived the available support as insufficient to meet student needs. The study concluded that a gap exists between the availability of mental health services and students’ ability to access and utilise these services effectively. Greater institutional visibility of services reduced structural barriers, and the development of a comprehensive, contextually responsive mental health policy was identified as a key priority for strengthening mental health support at Rhodes University.
Keywords: Mental health (http://id.loc.gov/authorities/subjects/sh85083615); Mental health services (http://id.loc.gov/authorities/subjects/sh85083636); Phenomenology (http://id.loc.gov/authorities/subjects/sh85100683); Pharmacy students (http://id.loc.gov/authorities/subjects/sh2009007390); Universities and colleges--South Africa (http://id.loc.gov/authorities/subjects/sh85141086); Pharmacy Practice; Lived experience (https://www.wikidata.org/wiki/Q1355387)